Mutational analysis of structure - function interactions within selected sites on the Escherichia coli ribosome - Belotserkovsky, Jaroslav Michailovich (My University, 2006)
Mutations were sought in Escherichia coli ribosomal RNA and ribosomal proteins that confer dependence to the antibiotic streptomycin, using both newly available as well as well-established genetic systems. I found that a classical ribosomal mutant, Sm-D3, was streptomycin dependent and had an additional mutation in another ribosomal component – protein L7/L12. The double mutant had an 8-fold lower streptomycin requirement as compared to Sm-D3 with a wild-type rplL. This supported a functional involvement of L7/L12 in the decoding center of the ribosome.
Master of Science - Adult Education
Keywords: escherichia; coli; ribosome; mutational